2010
DOI: 10.1111/j.1365-2052.2010.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p.C430S polymorphism in the PPARGC1A gene on muscle fibre type composition and meat quality in Yorkshire pigs

Abstract: The peroxisome proliferator-activated receptor-gamma coactivator-1A (encoded by PPARGC1A) is involved in the formation of type I fibres. Therefore, the PPARGC1A gene can be considered as a functional candidate gene for muscle fibre type composition and meat quality in pigs. The aim of this study was to investigate the associations of the p.C430S polymorphic site in exon 8 of the PPARGC1A gene with muscle fibre characteristics and meat quality traits. The polymorphism was genotyped by PCR-RFLP using AluI restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…FHL1 has been identified as a regulator of skeletal muscle mass [57]. PPARGC1A was considered as a functional candidate gene for muscle fiber type composition and meat quality in pig [58]. ANKRD1 and MYOZ2 were found to be related to muscular dystrophy [59], [60].…”
Section: Discussionmentioning
confidence: 99%
“…FHL1 has been identified as a regulator of skeletal muscle mass [57]. PPARGC1A was considered as a functional candidate gene for muscle fiber type composition and meat quality in pig [58]. ANKRD1 and MYOZ2 were found to be related to muscular dystrophy [59], [60].…”
Section: Discussionmentioning
confidence: 99%
“…These accumulating SNP data not only provide candidate genetic markers for breed selection of farm animals, but also lead to mechanistic understanding of how external factors regulate fiber type diversity. For instance, several SNP, identified in the gene PPAR γ coactivator 1 α ( PGC-1a ), a transcriptional coactivator enriched in type I fiber, can affect muscle fiber characteristics and meat quality traits of pigs (Lin et al, 2002; Haegeman et al, 2003; Kim et al, 2010; Lee et al, 2011). It has been shown that PGC-1α-induced fiber type switching is mediated by and requires hypoxia-inducible factor 2α ( HIF2α ), and ablation of HIF2 α in differentiated myocytes using myogenin-cre driver mice resulted in the switch of slow fiber type toward fast fiber type (Rasbach et al, 2010).…”
Section: Regulation Of Muscle Fiber Type Composition and Meat Productmentioning
confidence: 99%
“…In contrast, investigations in swine revealed significant effects of nucleotide variation at the PPARGC1A locus on muscle fiber characteristics and meat quality traits (e.g. 135-137. Erkens et al (2008) 138 described two novel splice variants of porcine PPARGC1A that were also detected in human tissue.…”
Section: Myokines - An Emerging New Class Of Secreted Proteinsmentioning
confidence: 99%